Control de la cuenta de existencia de la Sub Zona de Policía Los Ríos N. º 12 - Laborda Vera, Angélica Pamela (2020)
The case study demonstrates the analysis of the existence control process of the Los Ríos Police Sub-Zone No. 12, of group 1 3 Investments for Consumption Production and Marketing and sub accounts of the Inventory for Current Consumption, from its entry into the area of warehouse until its accounting treatment, said entity manages a second level management model that is due to the Decentralized Operating Entities (EOD), therefore its accounting treatment of the inventory account ends with the registration in the Integrated Financial Management System (eSIGEF ). The legal basis is determined, consisting of: Laws, Regulations, Government Regulations, which explain how to proceed with the control of stocks and their physical verification. Due to the lack of knowledge, non-application of the legal bases and the lack of an “inventory-kardex” control system, insufficient control of inventories is generated at the entry and exit of office materials, cleaning and printing, and spare parts and accessories for the Warehouse area, and no physical verification. Likewise, the activities to be followed for the respective accounting adjustment of the stocks between the physical and the accounting and the management sub-process for the physical verification are described.